The Effect of Flashcards in Improving Vocabulary at the Eighth Grade Students of SMP Negeri 6 Palu - Ba'dung, Yudit; Suriaman, Aminah; Rita, Ferry (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2024)
Students face challenges in English communication primarily due to insufficient vocabulary. Consequently, teachers should actively implement strategic measures to enhance students' mastery of vocabulary, such as incorporating activities like the use of flashcard. The objective of this study is to investigate whether the utilization of flashcard media has a positive impact on enhancing vocabulary. This research is an experimental study with a pre post test design using 2 sample groups, namely the intervention group and the control group consisting of 32 people per group. In choosing the participants, the researcher used purposive sampling. This study was conducted in SMPN 6 Palu since the participants are the students of the eighth grade. The results were analyzed using t table and t calculations to determine the effect. The result showed that the mean score of pre-test of control group is 45.13 and that the mean score post test of control group was 53, whereas the mean score of pre-test of experimental group is 45.38, and the mean score of experimental group was 81.38. t-counted (14.57) is higher that t-table (1.9988). This implies that the research hypothesis has been validated. In summary, the utilization of flashcards proves to be effective in enhancing vocabulary among eighth-grade students at SMP Negeri 6 Palu. flashcard media could be used as one of media in the classroom, because it easy and interesting in applying for the students.